2022
DOI: 10.3389/fmicb.2022.838207
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in the Characteristics of Klebsiella pneumoniae ST101 of Human, Environmental, and Animal Origin

Abstract: BackgroundKlebsiella pneumoniae ST101 is an emerging high-risk clone which exhibits extensive drug resistance. Bacterial strains residing in multiple hosts show unique signatures related to host adaptation. In this study, we assess the genetic relationship of K. pneumoniae ST101 isolated from hospital samples, the environment, community, and livestock using whole genome sequencing (WGS).Materials and MethodsWe selected ten K. pneumoniae ST101 strains from hospitalized patients in Italy (n = 3) (2014) and Spain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 50 publications
1
10
0
1
Order By: Relevance
“…2019; De Koster et al . 2022). Additionally, human ST101 colistin‐resistant K. pneumoniae clones have recently been identified in France (Jayol et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2019; De Koster et al . 2022). Additionally, human ST101 colistin‐resistant K. pneumoniae clones have recently been identified in France (Jayol et al .…”
Section: Resultsmentioning
confidence: 99%
“…The remaining strain belonged to ST147 and harboured the matallo-cabapenemase NDM-1 and the CTX-M-15 ESBL enzymes. The clonal lineage ST101 has been identified in several North Africa studies (Kieffer et al 2018;Yousfi et al 2018) and represents one of the high-risk MDR K. pneumoniae clones associated with carbapenemase (NDM-1, OXA-48) (Jaidane et al 2017;Yang et al 2019;De Koster et al 2022). Additionally, human ST101 colistin-resistant K. pneumoniae clones have recently been identified in France (Jayol et al 2014), whilst the ST147 K. pneumoniae clone has been reported worldwide, in association with numerous ESBL and carbapenemase genes.…”
Section: Colistin Resistance In North Africamentioning
confidence: 99%
“…This is in accordance with recent studies that showed most hospital-associated strains were resistant to last resort antimicrobials such as carbapenems, while livestock associated isolates were not. 13, 14, 34, 35…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with recent studies that showed most hospital-associated strains were resistant to last resort antimicrobials such as carbapenems, while livestock associated isolates were not. 13,14,34,35 We compared the clonal complexes of K. pneumoniae across three different niches to understand the distribution of these systematically collected isolates. The clonal distributions of K. pneumoniae were generally diverse within and between the niches (human, livestock, and hospital effluent samples).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, another high-risk MDR clone has been detected in animals in China . Klebsiella pneumoniae is an opportunistic pathogen that can infect humans and animals and is a common contaminant of retail meat, the increasing prevalence of MDR with virulence poses a potential threat to food safety, and animal and human health (De Koster et al 2022).…”
Section: Introductionmentioning
confidence: 99%